PENGARUH PELAKSANAAN K3 TERHADAP KINERJA KARYAWAN PADA PROYEK KONSTRUKSI DI KABUPATEN PURWODADI - Amrita Amrita; Agus B Siswanto; M. Afif Salim; Rizky Bintang Fauzi (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2023)
Implementing Occupational Health and Safety (K3) in a project is critically important because it will provide comfort and safety at work. Construction service providers as well as construction employees must be aware of this and must base it all on the existing regulations. Therefore, it is necessary to conduct research on K3 in construction projects, especially in the Purwodadi area. Due of a shortage of funding for K3, construction service providers pay less attention to K3 on some low-value construction projects. This study aims to identify K3 policies applied to construction projects in Purwodadi, determine and evaluate K3 elements and influences on employee performance, as well as identify and analyze the effect of K3 on project effectiveness and efficiency. K3 regulations are one of the components that are quite influential, K3 regulations are made so that they can be easily understood and implemented. There is a significant influence between K3 namely management commitment, regulations, worker competence, and employee involvement on employee performance. From this research, management’s response to K3 must be clear in the form of policies, regulations, assistance on equipment, training, supervision, and mitigation of any possible accidents that occur in the work environment.